Caring for pregnant women and babies in the context of the family healthcare program: an ethnographic study - Vania Bustamante; Cecilia Anne McCallum (Faculdade de Medicina de Botucatu (Unesp), 2010)
This study contributes to the conceptual discussion of healthcare, seen through an ethnographic approach to the care of pregnant women and newborns offered by health professionals working under the Family Health Program in a low-income neighborhood of Salvador, Brazil. Research involved Interviews and participant observation. In the article we analyze and compare professionals' and user's perspectives in two distinct contexts: The discovery of pregnancy and the decision to take it to completion; and attitudes and practices with respect to breast-feeding. We argue that, for both, care involves a permanent construction of "projects of the person". While professionals focus their interventions on women, seeking to implement guidelines and planned routines, users of the health centre resort to spontaneous behavior that attends to practical demands in which several relatives participate and where embodied experience is central. Differences between professionals and users are linked not only with subjective characters but with the social positions that they occupy.